Pengolahan dan Pemasaran Produk Pangan Lokal dalam Upaya Penanganan Stunting di Desa Lamajang, Kabupaten Bandung - Suryawardani, Bethani; Raharjo, Tito Pandu; Sunantri, Yudy (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Lamajang Village is a village located in Pangalengan District, Bandung Regency, West Java, which has a high stunting rate problem faced by the community in Lamajang Village. Stunting is characterized by stunted height at the age of Toddlers (Infants Under Five Years) due to chronic malnutrition. One of the factors that influences the occurrence of stunting is inappropriate and unhealthy breast milk substitutes (MPASI). The selection and presentation of food for children must be appropriate to avoid stunting in children, especially those under 2 years of age. Based on the problems faced by target partners in Lamajang Village, the alternative community service solutions that our group offers are: (1) Providing a high-nutrition menu workshop in an effort to deal with stunting in Lamajang Village; (2) Providing marketing training for nutritious food products from the results of the workshop that will be held; (3) Providing alternative innovations in nutritious food menus that are arranged into a stunting menu recipe book. Community service activities will be carried out on Thursday, December 5, 2024 in the Lamajang Village Hall, Bandung Regency. The training and workshop activities were attended by 40 (forty) participants consisting of PKK mothers, Posyandu cadres and parents of children under 2 years of age. The results of this community service activity are in the form of training and workshops on handling stunting and producing an alternative MPASI menu book to prevent stunting cases. The implementation of this workshop was felt to be very beneficial for the community in Lamajang Village and residents were satisfied with the results of the participant satisfaction survey that had been given.ABSTRAKDesa Lamajang ialah desa yang terletak di Kecamatan Pangalengan, Kabupaten Bandung Jawa Barat yang memiliki permasalahan angka stunting yang tinggi yang dihadapi oleh masyarakat di Desa Lamajang. Stunting ditandai dengan tinggi badan yang terhambat pada usia BALITA (Bayi Di Bawah Lima Tahun) akibat dari kekurangan gizi yang kronis. Salah satu faktor yang mempengaruhi pada kejadian stunting adalah makanan pengganti ASI (MPASI) yang kurang tepat dan kurang sehat. Pemilihan dan penyajian makanan untuk anak-anak harus tepat untuk menghindari stunting pada anak khususnya di bawah 2 tahun. Berdasarkan permasalahan-permasalahan yang dihadapi mitra sasar di Desa Lamajang, maka alternatif solusi pengabdian masyarakat yang kelompok kami tawarkan yaitu: (1) Memberikan workshop menu bergizi tinggi dalam upaya penanganan stunting di Desa Lamajang; (2) Memberikan pelatihan pemasaran produk makanan bergizi dari hasil workshop yang akan dilaksanakan; (3) Memberikan alternatif inovasi menu-menu makanan bergizi yang disusun ke dalam buku resep menu stunting. Kegiatan pengabdian Masyarakat dilaksanakan pada Kamis, 5 Desember 2024 di Aula Desa Lamajang, Kabupaten Bandung. Kegiatan pelatihan dan workshop diikuti oleh 40 (empat puluh) orang peserta yang terdiri dari ibu-ibu PKK, Kader Posyandu dan Orang Tua anak-anak dengan usia di bawah 2 tahun. Hasil kegiatan pengabdian masyarakat ini adalah berupa pelatihan dan workshop penanganan stunting serta menghasilkan buku menu alternatif MPASI untuk mencegah kasus stunting. Pelaksanaan workshop ini dirasakan sangat bermanfaat bagi masyarakat di Desa Lamajang dan warga puas dari hasil survei kepuasan peserta yang telah diberikan.